Persepsi pelajar bukan Muslim terhadap pembelajaran bahasa Arab - non-Muslim students’ perception towards learning Arabic language - Nasir, Mohd Shahrizal; Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri (Universiti Kebangsaan Malaysia (UKM), 2017)
Learning Arabic language in Malaysia involved various levels of education such as in schools, higher education institutions and the public. Arabic learners have a specific goal in learning the language which is related closely to Islam. Nowadays, the Arabic language learning also involves non-Muslim in various levels of education including higher education institutions. Thus, this article will discuss the perception of non-Muslims towards learning the Arabic language. The objective of this study is to explore their perceptions of learning Arabic language in order to ensure that the content of Arabic learning in line with the purpose of learning the language. This study is a qualitative study involving interviews with seven non-Muslim students studying Arabic at Universiti Sultan Zainal Abidin (UniSZA). The findings showed that all respondents gave a positive response in learning the Arabic language. The responses given involve the teaching methods practiced in order to master the Arabic language and to gain motivation in learning the language. All these responses indicate that the perception of non-Muslims towards learning Arabic language is positive if the learning process can be carried out properly and effectively. Some of the suggestions which are related to teaching Arabic language for nonMuslim students are also discussed in this article as an input that can be used by teachers of the Arabic language.